2021
DOI: 10.1038/s41598-021-99280-2
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion/lymphovascular invasion double positive predicts distant metastasis and poor survival in T3–4 oral squamous cell carcinoma

Abstract: Postoperative adjuvant therapy has been indicated by advanced T classification for T3–4 oral squamous cell carcinoma (OSCC) and the significance of perineural invasion (PNI) and lymphovascular invasion (LVI) in treatment for T3–4 OSCC remains unclear. Ninety-eight cumulative patients with T3–4 OSCC who underwent curative surgery between Jan 2002 and Dec 2010 were recruited and analyzed. Twenty-seven (27.6%) patients were PNI/LVI double positive. PNI/LVI double positive demonstrated independent predictive value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
3
11
1
Order By: Relevance
“…Histopathologic analysis found poorly‐differentiated tumors in the sample to have the greatest association with LVI, concuring with a well established clinical concept 10,18 . In agreement with Fania et al, 1 ulceration and dysplasia were also dominant features across the sample with severe dysplasia found most frequently in LVI positive cases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Histopathologic analysis found poorly‐differentiated tumors in the sample to have the greatest association with LVI, concuring with a well established clinical concept 10,18 . In agreement with Fania et al, 1 ulceration and dysplasia were also dominant features across the sample with severe dysplasia found most frequently in LVI positive cases.…”
Section: Discussionsupporting
confidence: 86%
“… 4 The presence of lymphovascular invasion is known to be a poor prognostic marker in various cancers including breast, urothelial and oral SCC. 5 , 6 , 7 , 8 , 9 , 10 In addition, the presence of LVI is associated with advanced tumor stage, high grades, lymph node metastasis in these cancers. 10 , 11 , 12 However, the molecular mechanisms mediating this prognostic feature remain undefined.…”
Section: Introductionmentioning
confidence: 99%
“…More than one-half of the patients were positive for LVI in the present study. This was similar to a study by Ting et al ( 98 ), which reported that most patients with T3–4 OSCC (44.9%) demonstrated LVI.…”
Section: Discussionsupporting
confidence: 92%
“…Roberts et al analyzed 12,437 cases of postoperative head and neck cancer in the Surveillance, Epidemiology, and End Results database from 2004 to 2012 [ 13 ], and found that the number of lymph nodes, an indicator of lymph node burden, was also correlated with short OS time. LVI and PNI were reported to be other adverse postoperative pathological features with poor survival outcomes [ 14 16 ]; however, the association was not observed in the present study, which was possibly caused by the small sample size of the patients with LVI or PNI.…”
Section: Discussioncontrasting
confidence: 89%